Remarkable catalytic activity of a sulfonated mesoporous polymer (MP-SO3H) for the synthesis of solketal at room temperature. (6th June 2017) - Churipard, Sathyapal R.; Manjunathan, Pandian; Chandra, Prakash; Shanbhag, Ganapati V.; Ravishankar, Raman; Rao, Peddy V. C.; Sri Ganesh, Gandham; Halgeri, A. B.; Maradur, Sanjeev P.
Abstract : A sulfonic acid-functionalized mesoporous polymer (MP-SO3 H) catalyst was prepared via post-synthetic modification of mesoporous polydivinylbenzene. Abstract : A sulfonic acid-functionalized mesoporous polymer (MP-SO3 H) catalyst was prepared via post-synthetic modification of mesoporous polydivinylbenzene by incorporating a sulfonic acid moiety using conc. H2 SO4 . The synthesized materials were characterized via several physicochemical techniques and their performance was evaluated for the room-temperature liquid-phase acetalization of glycerol with acetone. The MP-SO3 H catalyst performed better than other conventional solid acid catalysts, with a 94% glycerol conversion and 98.5% selectivity for solketal. The high activity of the MP-SO3 H catalyst was attributed to the facile diffusion of reactants and products in the mesoporous environment as well as to the high acidity. Glycerol conversion increased with increase in the total acidity of the catalyst. In addition, the acidity and surface density of (H + ) ions were found to have a direct correlation with the catalyst performance.